2019
DOI: 10.1029/2018jd029383
|View full text |Cite
|
Sign up to set email alerts
|

Scaling, Anisotropy, and Complexity in Near‐Surface Atmospheric Turbulence

Abstract: The development of a unified similarity scaling has so far failed over complex surfaces, as scaling studies show large deviations from the empirical formulations developed over flat and horizontally homogeneous terrain as well as large deviations between the different complex terrain data sets. However, a recent study of turbulence anisotropy for flat and horizontally homogeneous terrain has shown that separating the data according to the limiting states of anisotropy (isotropic, two‐component axisymmetric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 59 publications
(125 reference statements)
1
41
0
2
Order By: Relevance
“…Although from the physical point of view length scales are more appealing, time-scales are usually preferred for point measurements, because the time-space transformation is hampered by the inapplicability of Taylor's hypothesis to submeso motions [10]. Thus, in agreement with other authors [11,31,19], we use this fixed-time-scale separation recognizing, however, that the spectral gap is not always observed and that a residual submeso contribution may affect the range T < 100 s, especially for large stability. Figure 1 shows the stability dependence of the submeso parameters for the second-order moments involved in the uw budget, Eq.…”
Section: The Submeso Parametersupporting
confidence: 73%
See 1 more Smart Citation
“…Although from the physical point of view length scales are more appealing, time-scales are usually preferred for point measurements, because the time-space transformation is hampered by the inapplicability of Taylor's hypothesis to submeso motions [10]. Thus, in agreement with other authors [11,31,19], we use this fixed-time-scale separation recognizing, however, that the spectral gap is not always observed and that a residual submeso contribution may affect the range T < 100 s, especially for large stability. Figure 1 shows the stability dependence of the submeso parameters for the second-order moments involved in the uw budget, Eq.…”
Section: The Submeso Parametersupporting
confidence: 73%
“…In this sense, T = 100 s is the time scale that separates small-scale turbulence (T < 100 s) and submeso motions (T > 100 s). In the SBL, an averaging time ∼ 100 s has been used by several authors [e.g., 10,17,18,4,19]. To quantify the strength of the submeso effect (Sect.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…Interestingly, this route does not involve purely two‐component axisymmetric turbulence, but is more of an axisymmetric oblate type. However, Stiperski et al () show that the lack of small‐scale two‐component axisymmetric turbulence is often observed in other datasets. An interesting future analysis would be to investigate the scale‐wise return to isotropy in parallel with our results on the persistence and dimension of the dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Model uncertainty is a vexing problem in the wind energy industry. It has been shown that the so-called 'universal' model parameters are outdated and can no longer serve their purpose in efficiently predicting and extrapolating meteorological properties (Sfyri et al, 2018;Stiperski et al, 2019). This problem can be mitigated by the use of machine learning tools which have made great strides in the past few decades.…”
Section: Discussionmentioning
confidence: 99%